Response of Indian bread wheat (Triticum aestivum L.) to herbicides, their tank mixtures and phosphorus sources - Chhipa, K. G.; Nepalia, V. (Annals of Agricultural Research, 2016)
A field experiment was conducted during winter (rabi) seasons of 2005-06 and 2006-07 to find out the effect of broad-leaved herbicides and their mixtures with isoproturon and phosphorus sources on productivity of Indian bread wheat. The weed control herbicidal treatments comprised 2,4-D (500 g/ha), triasulfuron (15 g/ha), carfentrazone (20 g/ha) and isoproturon (750 g/ha), tank mixtures of isoproturon with 2,4-D, triasulfuron and carfentrazone and weedy check, while the three phosphorus sources were DAP, SSP and Phosphate Rich Organic Manure (PROM). The results showed that application of herbicide mixture comprising carfentrazone + isoproturon resulted in minimum density and dry matter of weeds with 96.36 and 96.87 % weed control efficiency during two successive years. This treatment also recorded the highest yield of wheat (5.72 and 5.91 t/ha) and highest net returns and B: C ratio in both the years. Among phosphorus sources, SSP registered maximum grain yield (4.92 and 5.04 t/ha), returns and benefit: cost ratio as compared to DAP and PROM.